Transient flow boiling in a semi-annular duct: From the Onset of Nucleate Boiling to the Fully Developed Nucleate Boiling. (August 2019) - Scheiff, V.; Baudin, N.; Ruyer, P.; Sebilleau, J.; Colin, C.
Highlights: Infra-red (IR) measurements are synchronized with high-speed camera visualizations. A time scale related to flow dynamics characterizes the transient heat convection. Space-time diagrams of wall temperature allows a better understanding of the ONB. A very strong time and space variation of the wall heat flux is observed. The overheated wall temperature at ONB is well predicted by modified Hsu's model. Abstract: This paper presents an investigation of the transient Onset of Nucleate Boiling (ONB) on a vertical heated surface cooled by an upward flow. The duct geometry used (semi-annulus with a heated inner wall) make this study very similar to a fuel rod in a Pressurised Water Reactor (PWR). This test section is then heated with different power steps to show the ONB and observe its propagation along the wall. The fluid used is the refrigerant HFE7000 flowing with flow rates corresponding to Reynolds numbers from 0 to 60, 000 and subcoolings Jakob numbers from 8 to 33. Synchronised infra-red (IR) thermal measurements and high-speed camera visualizations provided new data which helped to develop models to characterise the Onset of Nucleate Boiling and the transition to the Fully Developed Nucleate Boiling regime (FDNB). This very finely characterized local behaviour provides an original insight for the onset of nucleate boiling in such sub-cooled convective configuration. It is shown that boiling is initiated by nucleation at a few specific sites and then propagates in the wake of a large vapor pocket flowing along the wall. Analysis of wall to fluid heat transfer evidences a short heat transfer degradation phase below the first vapor pocket, followed by a very effective cooling in its wake. The wall to fluid heat transfer during this transition toward fully developed nucleate boiling appears uncorrelated to the power dissipated within the heating element or to flow conditions.